Acid–induced Favorskii–type Reaction: Regiocontrolled Elimination of Acyloin Mesylates Leading to α, β‐Unsaturated Ketones and Application to Formal Total Synthesis of (R)‐Muscone from Racemic Muscone. Issue 12 (9th August 2016) - Ashida, Yuichiro; Tanaka, Akihiro; Hosomi, Kohei; Nakamura, Atsushi; Misaki, Tomonori; Nakatsuji, Hidefumi; Tanabe, Yoo
Abstract: A highly regiocontrolled acid‐induced Favorskii‐type elimination reaction using unsymmetrically‐substituted acyloin mesylates proceeded smoothly to give more substituted α, β‐unsaturated ketones under mild conditions. Not only acyclic mesylates but also cyclic acyloin mesylates produced the corresponding higher substituted (thermodynamically stable) α, β‐unsaturated ketones via distinctive double‐bond‐migration pathway. The regioselectivity is nearly exclusive in all 8 examples examined. A plausible fundamental pathway for this regiocontrolled elimination is proposed; (1) isomeric enol and/or cyclopropane formations proceeds to give the cationic intermediate and/or the cyclopropane intermediate, respectively, (2) successive crucial step for regioselective MsOH (or H2 O) elimination concomitant with specific proton withdrawal leads to the corresponding intermediates, the major E1'‐like dienol and the minor E1‐like dienol, (3) final tautomerization affords more substituted α, β‐unsaturated ketones. Mechanistic speculations for the plausible mechanism and exo / endo selectivity for cyclic acyloin mesylates are also described. The present reaction was applied to a successful synthesis of "chiral" ( R )‐muscone precursor from readily available "racemic" muscone. Abstract : A highly regiocontrolled acid‐induced Favorskii‐type elimination reaction using unsymmetrically‐substituted acyloin mesylates proceeded smoothly to give more substituted α, β‐unsaturated ketones under mild conditions via distinctive double‐bond‐migration pathway. A mechanistic speculation and an application to the synthesis of ( R )‐muscone precursor are also described.